O significado das acções colectivas de repertório tradicional na I República - David Luna de Carvalho (Ler História, 2010)
The Author examines the popular resistance to the laicization of the State and public life on the mainland, Madeira and the Azores between 1910 and 1917. He defines the existence of five types of collective actions of traditional repertoire according to their motivations: actions in the political-religious sphere; medical and sanitarian; education and schools; political and military; and finally, economic and social. Even in cases of collective action in economic and social grounds, there is strong evidence that they crossed with motives from the political-religious.